Functional improvement in individuals with chronic spinal cord injury treated with 4-aminopyridine: A systematic review - Paredes-Cruz, Martin; Grijalva, Israel; Martínez-López, Yoscelina Estrella; Guizar-Sahagún, Gabriel; Colín-Ramírez, Eloisa; Rojano-Mejía, David (Frontiers in Neurology, 2022)
Study design Systematic review. Objective To provide current evidence on the efficacy of 4-aminopyridine (4-AP) to bring about functional improvement in individuals with chronic traumatic spinal cord injury (SCI). Methods The Medline (PubMed), Web of Science and SCOPUS databases were systematically searched for relevant articles on the efficacy of 4-AP to treat SCI, from the dates such articles were first published until May 2022. Full-text versions of all the articles selected were examined independently by two reviewers. Methodological quality was rated using the Modified Jadad Scale, and risk of bias was assessed with the RoB-2 test. Data extracted included human models/types, PRISMA assessment protocols, and the results of each study. Descriptive syntheses are provided. Results In total, 28 articles were initially identified, 10 of which were included after screening. Most of the studies reviewed reported some degree of patient improvement in one or more of the following parameters: motor, sensitivity and sexual function, sphincter control, spasticity, ability to function independently, quality of life, central motor conduction, pain, and pulmonary function. Conclusions This review confirms the efficacy of 4-AP in improving several conditions resulting from SCI but further research on this topic is warranted. Additional randomized clinical trials with 4-AP involving larger sample sizes are needed, as are consistent outcome measures in order to obtain adequate data for analysis with a view to enhance treatment benefits. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=334835, PROSPERO CRD42022334835.